Association of the number of minor hallucinations and well-structured visual hallucinations in Parkinson’s disease - Haiying Zhang; Yang Zhao; Yi Chen; Yuanyuan Feng; Bo Shen; Shuangshuang Dong; Jun Zhu; Xu Jiang; Dongfeng Li; Yaning Chen; Feng Han; Li Zhang (npj Parkinson's Disease)
Abstract Minor hallucinations (MH), comprising three subtypes (presence hallucinations, passage hallucinations, and visual illusions), typically emerge during the early stages of Parkinson’s disease (PD) and precede the onset of well-structured visual hallucinations (VH). Whether the number of MH is associated with VH in PD patients remains unclear. We investigated the association between the number of MH and VH in 372 PD patients. Log-binomial regressions showed that individuals with multiple MH had a significantly higher prevalence of VH (RR = 2.08, 95% CI: 1.11–3.90 for 2 MH; RR = 6.20, 95% CI: 3.40–11.31 for 3 MH), while those with only one MH had a similar VH prevalence compared to those without MH (RR = 1.08, 95% CI: 0.53–2.21). Women exhibited stronger associations than men. These findings emphasize the importance of quantifying MH subtypes when assessing hallucinations, though their potential utility as predictive markers of disease progression and targets for early intervention requires validation through longitudinal studies.